2013
DOI: 10.1038/nm.3161
|View full text |Cite
|
Sign up to set email alerts
|

Mining exomic sequencing data to identify mutated antigens recognized by adoptively transferred tumor-reactive T cells

Abstract: Significant tumor regressions have been observed in up to 70% of patients receiving adoptively transferred autologous melanoma-reactive tumor infiltrating lymphocytes (TIL) 1,2, and in pilot trials, 40% of treated patients experienced complete regressions of all measurable lesions for at least five years following treatment 3. To evaluate the potential association between the ability of TIL to mediate durable regressions and their ability to recognize potent antigens that presumably include mutated gene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
831
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 992 publications
(848 citation statements)
references
References 30 publications
10
831
2
5
Order By: Relevance
“…most are not immunogenic. 24,28,46 Especially in patients with high mutational load, hundreds or even thousands of mutated peptides are commonly found based on sequencing approaches, highlighting the need to further narrow down this candidate list and increase the specificity in detecting immunogenic neoepitopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…most are not immunogenic. 24,28,46 Especially in patients with high mutational load, hundreds or even thousands of mutated peptides are commonly found based on sequencing approaches, highlighting the need to further narrow down this candidate list and increase the specificity in detecting immunogenic neoepitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the peptides from the NCI dataset were also published, 46,6163 which resulted in an overlap with the curated literature dataset. To keep the datasets distinct from each other, we filtered the literature dataset and removed all peptides included in the NCI dataset for all bioinformatics and statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…These studies demonstrate that neoantigens can be rapidly identified within a few weeks and can serve as tumor-specific targets for T cell-mediated recognition and destruction of tumor cells. Similarly, several neoantigens have been identified from human cancer recognized by CD8 + and CD4 + T cells through exome sequencing and screening for T cell responses [221][222][223]. More recently, it has been further demonstrated that neoantigen-specific T cells can be isolated from patient PBMCs using FACS analysis and purification, although their frequencies are much lower than neoantigen-specific T cells in the corresponding TIL populations [45,224].…”
Section: The Second Wave Of Tumor Antigen Discovery: Mutation-derivedmentioning
confidence: 99%
“…In subsequent validation steps, tumor-reactive T cells are the key to screening and identification of T cell-recognized neoantigens (Table 3). TILs can be isolated from freshly obtained tumor tissues and used for screening candidate neoantigens [221]. Alternatively, neoantigen-specific T cells may be isolated from the patient's PBMCs based on upregulation of activation markers such as 4-1BB, OX-40 and PD-1 on T cells [224,235].…”
Section: Identifying Neoantigens Recognized By Cd8 + T Cellsmentioning
confidence: 99%
“…First, in-depth evaluation of the T-cell response in melanoma patients who responded to TIL-therapy, and infusion of ex vivo expanded tumor-infiltrating T cells, revealed that the T-cell clones driving therapeutic efficacy were not directed against lineage-specific and cancer testis antigens, but instead against neo-epitopes encoded by the tumor mutanome [3]. Essentially the same observation was subsequently made in patients responding to so-called checkpoint inhibitors, antibodies against cytotoxic T-lymphocyte-associated Protein 4 (CTLA-4) or the programmed cell death (PD)-1/PD-L1 axis, that can activate T cells by neutralizing inhibitory pathways in T cells [4].…”
mentioning
confidence: 99%